Response of young plants of four conifer species to mercury exposure - Altonar-Gómez, Ximena Aurora; Tzintzun-Pedraza, Karen Ximena; Osuna-Vallejo, Verónica; Lindig-Cisneros, Roberto (Instituto de Ecología, A.C., 2021)
Physical-chemical properties of mine residues tend to prevent soil formation processes and plant growth. Nevertheless, there are plant species capable of growing in polluted environments and absorbing heavy metals. In Tlalpujahua, Michoacán, as in many mining sites, there are sites polluted with mercury because of the metal refining processes. We studied the effect of mercury in the growth medium in young conifer plants of Pinus devoniana Lindley, Pinus pseudostrobus Lindley, Pinus martinezii E. Larsen and, Juniperus deppeana Steud. Young plants of the four species were grown in media with four levels of mercury and three growth related response variables were recorded. Pinus devoniana and Pinus pseudostrobus had a reduction in growth when the concentration of mercury in the medium was 15 ppm or higher. Roots of P. devoniana had lower biomass when exposed to mercury than control plants. P. martinezii was resistant to mercury. J. deppeana had an intermediate resistance to mercury with high variation among individuals. Results indicate that J. deppeana and P. martinezii are species tolerant to mercury exposition and can be useful for reclamation of contaminated sites.